Prevalence of Non-albicans candida and its drug susceptibility pattern isolated from a tertiary care hospital, Karnataka - R, Shyamala; Parandekar, Prashanth K (Annals of Pathology and Laboratory Medicine, 2015)
Background: Candida infections have increased over the past few decades. Candida species are opportunistic yeast infections which are also common commensal of human gastro-intestinal tract. It causes spectrum of diseases extending from Mucocutaneous infections to systemic infection with dissemination. The increased incidence of life threatening infections in immunocompromised hosts and the emergence of non albicans candida (NAC) have made the treatment options difficult. Over to it, rampant use of azoles as prophylaxis has led to the emergence of azole resistant strains which are of great concern for clinical and therapeutic aspects. The present study was taken up with the aim to isolate and identify the candida species from clinical samples using a chromogenic media and to derive anti-fungal susceptibility pattern. Methods: Total 484 samples was processed using Hichrome agar media and idenfied using standard identification methods up to species level. Antifungal susceptibility tests were performed according to CLSI guidelines for Fluconazole, Voriconazole, Ketoconazole and Itraconazole. Results: Total 484 clinical specimens was collected from all the department. Out of which 176 candida species was isolated. Predominant isolate was C. tropicalis followed by C. guilliermondi and C. parapsilosis. Hichrome agar showed good sensitivity and specificity. Voriconazole (77.5%) showed good sensitivity over Fluconazole (41.4%) sensitivity. Conclusion: present study highlights there is need to identify NAC and give sensitivity pattern.